Literature Review of An Islamic Positive Work Behavior: Ta’awun - Siti Nur Azizah; Sri Wahyuningsih; Aris Susetyo (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2023)
Positive behavior in the workplace is expected to be capable of completing the organization more effectively and increasing performance. One of the Islamic concepts about this behavior is ta'awun which is taken from the Qur'an and means helping each other in doing good. This research is a bibliographical search and is used by researchers to find sources of citations using citation techniques. There are many studies related to ta'awun, researchers agree that 4 indicators of ta'awun behavior are helping co-workers without being asked, helping with work even though it is not their job, helping co-workers is worship, and helping co-workers without expecting anything in return. Positive behavior in the workplace is expected to be capable of completing the organization more effectively and increasing work performance.